Pengaruh Stres Kerja Terhadap Kinerja Karyawan di Four Points By Sheraton Bali, Seminyak - Maesa, I Ketut Pasek Krisna; Sabudi, I Nyoman Sukana; Sulistyawati, Ni Luh Ketut Sri (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
This study aims to investigate the effect of job stress on employee performance at Four Points by Sheraton Bali, Seminyak. Data was obtained through questionnaires involving all 75 employees as respondents, using the saturated sample method. The results showed that job stress has a negative and significant impact on employee performance. Data analysis was conducted using the coefficient of determination, T test, and simple linear regression analysis. The T test shows that the value of work stress (X) is -0.768 with a significance value of 0.000. The coefficient of determination indicates that work stress affects employee performance by 51.5%, while the remaining 48.5% is influenced by other variables not included in this study.